ILCA's Documentation Centre: An information service for African livestock research - Hailu, M. (OAU, 1985)
Gives a brief description of the various activities of ILCA's Documentation Centre and the range of information service it provides to its users. Shows the date & no of documents of non-conventional literature collected by ILCA from various African countries, and country distribution of ILCA SDI users. Presents the request for literature search.